Canadian FDI in a post COVID-19 world: have we reached the tipping point?. Issue 1 (2nd January 2021) - Hejazi, Walid; Tang, Jianmin
Abstract: The highly contagious COVID-19 virus spread across the world in a matter of months, beginning in the second half of 2019 and being declared a global pandemic by March, 2020. To limit its continued spread, large parts of economies around the world were shut down, including in Canada and the USA. These actions resulted in levels of unemployment and contractions in GDP not seen since the Great Depression. Superimposed on these truly extraordinary events have been global supply challenges which manifested themselves in an inability of governments to procure critical medical equipment, which exacerbated the health care crisis, increased protectionist sentiments, and led to new protectionist legalisation across many countries. Furthermore, the COVID-19 shock will reinforce trends that were already present globally to shorten supply chains and slow FDI growth, serving as an important tipping point that should encourage governments to consider policies to mitigate the impact of such changes on host economies. This paper considers how these economic, financial, and legislative developments will likely impact FDI patterns for years to come.